2009
DOI: 10.1089/cap.2008.094
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for Weight Control in Pediatric Patients on Atypical Antipsychotic Medication

Abstract: Objective: Metformin was assessed as an interventional medication for weight gain in children and adolescents taking atypical antipsychotic agents. Method: A 12-week open-label trial was conducted to evaluate metformin's effectiveness and safety for weight management. Eleven subjects, ages 10-18 years, participated in the study. Each subject received metformin orally up to 2000 mg=day. Primary outcome measures included weight, body mass index (BMI), and waist circumference. Secondary outcome measures included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 17 publications
(14 reference statements)
1
25
0
1
Order By: Relevance
“…The findings suggest that metformin is an effective, safe, and well-tolerated therapy for weight gain and metabolic abnormalities induced by antipsychotics. Furthermore, most case reports [51][52][53] and open-label studies [54][55][56][57][58] in patients treated with antipsychotics also showed that adjunctive metformin was associated with a decrease in weight gain and reduction in metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that metformin is an effective, safe, and well-tolerated therapy for weight gain and metabolic abnormalities induced by antipsychotics. Furthermore, most case reports [51][52][53] and open-label studies [54][55][56][57][58] in patients treated with antipsychotics also showed that adjunctive metformin was associated with a decrease in weight gain and reduction in metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis of 32 placebocontrolled pharmacologic intervention trials involving 1482 subjects suggested that metformin had the most promising effect on weight loss, followed by fenfluramine, sibutramine, topiramate, and reboxetine [19]. Other clinical trials also showed a similar effect of metformin in attenuating SGA-induced weight gain [18,[20][21][22][23]. A recent study reported that both metformin and berberine treatment did not affect food intake, but significantly prevented olanzapine-induced brown fat loss [24].…”
Section: Introductionmentioning
confidence: 99%
“…In a 12-week, open-label trial of metformin for the treatment of weight gain and metabolic profiles in pediatric patients, Shin et al (50) studied 11 children and adolescents ages 10–18 years who received metformin orally up to 2000 mg/day. They reported no statistically significant reductions in mean weight, waist circumference, BMI, serum glucose, and insulin even though 5 of the 11 subjects lost weight.…”
Section: Introductionmentioning
confidence: 99%